HOSPITAL MANAGEMENT STRATEGIES IN PREVENTING ANTIBIOTIC RESISTANCE - Worung, Ivan Master; Joko Pitoyo; Purwadhi Purwadhi; Yani Restiani Widjaja (Journal of Innovation Research and Knowledge, 2024)
Introduction Antibiotic resistance is a challenge in health services in Indonesia. Data in 2019 by The World Health Organization (WHO) showed that around 4.95 million deaths were related to antibiotic resistance. Control of Antimicrobial Resistance in 2020-2024 based on the Vision of the National Action Plan (RAN) is a healthy Indonesia and free from the impact of antimicrobial resistance. Methods Literature Review conducted through articles published in the last 5 years. A review was conducted on articles related to management strategies in preventing antibiotic resistance. Articles taken as sources use English and Indonesian that are accredited by SCOPUS or accredited by SINTA. Finding Results Hospital strategy management to address antibiotic resistance such as development and implementation of antibiotic use policies, education and training, monitoring and evaluation of antibiotic use, infection control and prevention, appropriate use of diagnostic tests, infection and disease management, application of technology, and collaboration with external parties. Conclusion Antibiotic resistance in Indonesia and globally has become a problem that needs attention to prevent the occurrence of increasingly widespread antibiotic resistance. A good strategy will prevent antibiotic resistance from becoming more controlled so that it can have an impact on hospital services and also have a good impact on patients being treated.